Síntese e estudo das propriedades ópticas de heteroestruturas do tipo caroço/casca de CdS/ZnS para aplicação em dispositivos optoeletrônicos - Torres, Everton Tiago dos Santos (2019)
In this work, various sizes of CdS and CdS / ZnS semiconductor nanoparticles in a core / shell structure were synthesized using a hot injection synthesis route. How its optical and selected properties were analyzed by UV-Vis optical absorption, photoluminescence and transmission electron microscopy techniques. UV-Vis spectroscopy measurements were performed using CdS and CdS / ZnS to evaluate: a) if there was an occurrence, b) if several test sizes were used, c) an energy difference by the method and d) the effects of the passivation of the shell material on the core constituent material. Photoluminescence measurements (English - photoluminescence - PL) were used to study the fluorescence of the lamps and also to use the results to verify the material gap energies. Temperaturevarying PL measurements were performed to calculate the activation energy of nonradiative channels. The blue deviation in the PL and UV-Vis spectra indicates the formation of shell on the stone material. Measurements of PL economic efficiency (PLQY) and PL lifetime were performed and their results of non-radiative decay rates showed that the CdS structure was passivated by the ZnS shell.